From clinical symptoms to MR imaging: Diagnostic steps in adenomyosis - Krentel, Harald; Cezar, Cristina; Becker, Sven; Di Spiezio Sardo, Attilio; Tanos, V.; Wallwiener, Markus; Wilde, Rudy Leon de (BioMed research international, 2017)
Adenomyosis or endometriosis genitalis interna is a frequent benign disease of women in fertile age. It causes symptoms like bleeding disorders and dysmenorrhea and seems to have a negative effect on fertility. Adenomyosis can be part of a complex genital and extragenital endometriosis but also can be found as a solitary uterine disease. While peritoneal endometriosis can be easily diagnosed by laparoscopy with subsequent biopsy, the determination of adenomyosis is difficult. In the following literature review, the diagnostic methods clinical history and symptoms, gynecological examination, 2D and 3D transvaginal ultrasound, MRI, hysteroscopy, and laparoscopy will be discussed step by step in order to evaluate their predictive value in the diagnosis of adenomyosis.